AB176. Impact of squamous and/or glandular differentiation on recurrence and progression after transurethral resection for non-muscle invasive urothelial carcinoma of bladder - Xu, Hao (Transl Androl Urol, 2016)
OBJECTIVE: To investigate the impact of squamous and/or glandular differentiation on recurrence and progression in patients with non-muscle-invasive urothelial carcinoma of bladder (NMIUCB) following transurethral resection (TURBT). METHODS: A total of 869 patients with NMIUCB treated with TURBT at our institution from January 2006 to January 2011 were selected retrospectively for the analysis. Correlations among squamous and/or glandular differentiation with other clinical and pathological features were assessed by chi-square. Recurrence-free survival (RFS) and progression-free survival (PFS) curves were estimated using the Kaplan-Meier method. Univariate and multivariate analyses were performed through a Cox proportional hazards regression model. RESULTS: Among 869 consecutive patients, 232 (26.7%) patients had squamous and/or glandular differentiation. High grade tumors were more common in patients with squamous and/or glandular differentiation than those with pure UCB (P<0.001). Correlations between age (P=0.115), gender (P=0.184), tumor size (P=0.223), tumor multiplicity (P=0.108), pathological tumor stage (P=0.909) and squamous and/or glandular differentiation were not statistically significant. There was a statistically prominent tendency towards higher recurrence rate and shorter RFS time in patients with squamous and/or glandular differentiation. However, no statistically significant differences were observed in progression rate and PFS between the two groups. On multivariate Cox regression analysis, squamous and/or glandular differentiation was identified as an independent prognostic predictor of recurrence (HR 1.46, 95% CI, 1.10–1.92, P=0.008). CONCLUSIONS: The presence of squamous and/or glandular differentiation could be associated with higher recurrence rate and shorter RFS time in patients with NMUCB. It is an independent prognostic predictor of recurrence.